SARS-CoV-2 Breakthrough Infections after Third Doses Boost IgG Specific Salivary and Blood Antibodies - Badano, Maria Noel (2023)
SARS-CoV-2 breakthrough infections, associated with waning immunity, increase systemic antibody levels. In this study, we analyzed the impact of the infection timing on the magnitude of the systemic humoral response and whether breakthrough infections also boost antibody levels in the salivary compartment. We observed that the combination of infection plus vaccination, regardless of infection timing, produced a sharp increase in systemic antibodies, which were higher in subjects infected after third doses. Moreover, despite high systemic antibody levels, breakthrough infections after dose three occurred and boosted antibody levels in the salivary compartment. These results suggest that current vaccination strategies against COVID-19 should be improved. Results also showed that determination of salivary antibodies against SARS-CoV-2 could be a valuable tool in disease prevalence studies, for the follow-up of vaccinated individuals, and to assist vaccination strategies against COVID-19, especially in settings where blood sampling cannot be fulfilled.